A Preliminary Study: Applying Problem-Posing Learning Models on Algorithm and Flowchart Materials in Basic Programming Class - Aulia Akhrian Syahidi; Herman Tolle; Ahmad Afif Supianto; Tsukasa Hirashima (JKTP: Jurnal Kajian Teknologi Pendidikan, 2020)
Abstract: We propose the applying of the problem-posing learning model to find out the activities and student learning outcomes in learning algorithm and flowchart material in the basic programming class. This research is a preliminary study that will be used to develop applications/systems/interactive media/games that will support the operation of the problem-posing learning model automatically in the upcoming basic programming class. The classroom action research method was used with the implementation of two cycles involving 38 students in the first semester of vocational high school. The process of applying the problem-posing learning model uses the pre-solution posing type, which requires that each student make a question of the situation that is held, where students are expected to be able to make questions related to questions previously made by the teacher, then exchange the questions to other students to solve them.  The flow of making and solving questions is that students make the main case which then completes it in the form of algorithmic answers and also a flowchart assisted by the Raptor application. By applying the problem-posing learning model, it can be concluded that in cycle 1 and cycle 2 the achievement of learning activities and outcomes tends to be good. The success of this research can provide perspective and guidance for developing basic programming applications/systems/interactive media/games that will instill the problem-posing learning model in the interaction flow and can introduce students early on the problem-posing process.